The Role of Natural Additives on the Wear and Friction Proper-ties of Nanocomposites for Friction Applications - Mostafa Amirjan; Hassan Sakiani (Mechanics of Advanced Composite Structures)
In the present study, the effect of banana peel and bagasse particle additives on the friction and wear behavior of multi-ingredient friction material nanocomposites have been investigated. In order to develop optimized properties of friction nanocomposite, the type and content of natural additives were changed beside the constant amount of other constituents such as alumina nanoparticle and other functional ingredients. The microstructural investigation and wear test were performed. The results showed as the natural additive content increases, the density of nanocomposite, and the hardness decrease. The highest hardness and friction values and the lowest specific wear rate would be achieved for a composite sample with 5 wt. % of baggase additive.